Pengaruh Pemberian Niasin dan Kafein dalam Model Minuman Berenergi terhadap Fisiologi Hati Tikus Wistar Jantan (The Effect of Caffeine and Niacin Administration within Energy Drink Model towards Liver Physiology of Male Wistar Rat) - Ngurah Agung Reza Satria Nugraha Putra; Erma Sulistyaningsih; Jauhar Firdaus (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Recently,there are many hepatotoxicity case reports induced by energy drinks and its niacin content is assumed to be the cause of liver injury. Caffeine in energy drinks actually has a hepatoprotective effect. However, this hepatoprotective effect of caffeine is less potent in counteracting the hepatotoxic effect of niacin. This study aimed at determining niacin and caffeine influences in inducing the disruption of liver physiology and the dose of niacin and caffeine in energy drink model which can induce the disruption of liver physiology by measuring AST, ALT, and GGT. As many as 28 male albino wistar rats were divided into seven groups;1 control group and 6 experimental groups, for 49 days. At day 50th, the rats were terminated to measure the AST, ALT, and GGT. The AST and ALT enzyme levels were not significantly correlated (p> 0,05). Otherwise, the GGT enzyme level was significantly correlated (p<0,05). It was showed that niacin and caffeine elevate GGT enzyme at doses 0,491 mg/ 200gr body weight/ day niacin and 1,2275 mg/ 200gr body weight/ day caffeine. These doses are equal to the consumption of three packs of energy drinks per day in human. Keywords: niacin, caffeine, energy drinks, AST, ALT, GGT